Estudo fonético e fonológico da língua Yuhup - Fernandes, Dacyo Cavalcante [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
O trabalho consiste em um estudo fonético e fonológico da língua indígena Yuhup, pertencente à família linguística Nadahup e falada em territórios da região amazônica que se estendem por faixas do Brasil e da Colômbia. O levantamento dos dados foi efetuado em uma única viagem de campo, realizada em outubro de 2015. A metodologia emprega distintos recursos de análise, recorrendo ao estruturalismo norte-americano e modelos de fonologia não linear.

This work consists of a phonetic and phonological study of the Yuhup indigenous language, affiliated to the Nadahup family and spoken across Amazonic territories through Brazil and Colombia. Data collection was performed on a single fieldwork held in October 2015. The methodology utilizes different analytical resources, resorting to American structuralism and nonlinear phonology models. Besides introductory section and the conclusion, this work is divided into five sections that address: 1 theoretical-methodological aspects; 2 data on the people and language family; 3 phonemic study of sounds identified in the language; 4 the analysis of the syllabic structure according to non-linear phonology; 5 stress classification according to Hayes metrical theory (1995).
Phonetic and phonological study of Yuhup language
Keywords: Língua Yuhup; Família Nadahup; Fonologia